Leptin Receptor q223r Polymorphism Influences Clostridioides difficile Infection-Induced Neutrophil CXCR2 Expression in an Interleukin-1β Dependent Manner - Horrigan, Olivia; Jose, Shinsmon; Mukherjee, Anindita; Sharma, Divya; Huber, Alexander; Madan, Rajat (Frontiers in Cellular and Infection Microbiology, 2021)
Neutrophils are key first-responders in the innate immune response to C. difficile infection (CDI) and play a central role in disease pathogenesis. Studies have clearly shown that tissue neutrophil numbers need to be tightly regulated for optimal CDI outcomes: while excessive colonic neutrophilia is associated with severe CDI, neutrophil depletion also results in worse outcomes. However, the biological mechanisms that control CDI-induced neutrophilia remain poorly defined. C-X-C chemokine receptor 2 (CXCR2) is a chemotactic receptor that is critical in neutrophil mobilization from bone marrow to blood and tissue sites. We have previously reported that a single nucleotide polymorphism (SNP) in leptin receptor (LEPR), present in up to 50% of people, influenced CDI-induced neutrophil CXCR2 expression and tissue neutrophilia. Homozygosity for mutant LEPR (i.e. RR genotype) was associated with higher CXCR2 expression and more tissue neutrophils. Here, we investigated the biological mechanisms that regulate neutrophil CXCR2 expression after CDI, and the influence of host genetics on this process. Our data reveal that: a) CXCR2 plays a key role in CDI-induced neutrophil extravasation from blood to colonic tissue; b) plasma from C. difficile-infected mice upregulated CXCR2 on bone marrow neutrophils; c) plasma from C. difficile-infected RR mice induced a higher magnitude of CXCR2 upregulation and had more IL-1β; and d) IL-1β neutralization reduced CXCR2 expression on bone marrow and blood neutrophils and their subsequent accrual to colonic tissue. In sum, our data indicate that IL-1β is a key molecular mediator that communicates between gastro-intestinal tract (i.e. site of CDI) and bone marrow (i.e. primary neutrophil reservoir) and regulates the intensity of CDI-induced tissue neutrophilia by modulating CXCR2 expression. Further, our studies highlight the importance of host genetics in affecting these innate immune responses and provide novel insights into the mechanisms by which a common SNP influences CDI-induced neutrophilia.